The inspiration of methyltransferase in RNA methylation modification for targeted therapy of malignant tumors - Chen, Xinru; Liu, Xinyu; Xu, Jiaqi; Zhu, Xingyu; Liu, Bingyao; Yang, Xinhao; Cong, Ge; Lin, Xiaoyan; Chong, Wei; Chen, Hao (Frontiers in Immunology, 2025)
RNA methylation modification has always been a research hotspot. RNA methylation modification can regulate processes such as transcription, translation, splicing, stability, and degradation of RNA, in which effector proteins play an important role, including ‘writers’, ‘erasers’, and ‘readers’. There are various types of proteins involved in cancer progression, and in recent years, research on their mechanisms of action has been increasing, providing new ideas for targeted cancer therapy. By regulating the expression of related genes and affecting signaling pathways, protein writing plays a role in promoting or inhibiting cancer in the proliferation, invasion, migration, and metastasis of different tumors, providing direction for the treatment of malignant tumors. This article reviews the mechanisms of common RNA methylation modified writers and their prospects in targeted cancer therapy.